1996
DOI: 10.1029/96ja00682
|View full text |Cite
|
Sign up to set email alerts
|

Linear theory and modeling of the Rayleigh‐Taylor instability leading to the occurrence of equatorial spread F

Abstract: In a test of the generally accepted Rayleigh‐Taylor (R‐T) instability mechanism for equatorial spread F (ESF), a linear instability growth rate γRT is derived following the formalism of Haerendel (preprint, 1973) which takes into account the variations of physical parameters along geomagnetic flux tubes. The resulting form of γRT extends the results of previous work by including direct dependencies on transequatorial neutral winds, zonal electric fields, vertical and horizontal ionospheric density gradients, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
566
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(586 citation statements)
references
References 45 publications
19
566
0
1
Order By: Relevance
“…The plasma bubbles with shorter lifetimes in the present study were observed in October 2011 when solar activity approached maximum. Sultan [1996] derived the flux tube integrated growth rate of the generalized Rayleigh-Taylor instability:…”
Section: Discussionmentioning
confidence: 99%
“…The plasma bubbles with shorter lifetimes in the present study were observed in October 2011 when solar activity approached maximum. Sultan [1996] derived the flux tube integrated growth rate of the generalized Rayleigh-Taylor instability:…”
Section: Discussionmentioning
confidence: 99%
“…The results for magnetically disturbed periods are discussed below. The role of the vertical plasma drifts on the generation and evolution of these irregularities can be determined from their effects on the time integrated growth rate of the RayleighTaylor instability [e.g., Maruyanta, 1988; Sultan, 1996]. We can estimate these effects by examining the evening and nighttime Jicamarca average quiet time vertical drifts presented in Figure 7.…”
Section: Spread F During Premidnight Hoursmentioning
confidence: 99%
“…[21] Following Sultan [1996], a simplified expression for the Rayleigh-Taylor instability growth rate can be written as…”
Section: Modeling Investigation Of the Rayleigh-taylor Instability Grmentioning
confidence: 99%
“…Also, the nonzero field line integrated Pedersen conductivity of the E region was regarded as capable of affecting the growth rate. Subsequent modeling investigations evaluated the role of transequatorial neutral winds, zonal electric fields, density gradients, presence of an E region and chemical recombination on the flux tube integrated RT instability growth rate [Sultan, 1996].…”
Section: Introductionmentioning
confidence: 99%